2002
DOI: 10.1086/344048
|View full text |Cite
|
Sign up to set email alerts
|

The Magnification of SN 1997[CLC]ff[/CLC], the Farthest Known Supernova

Abstract: With a redshift of , SN 1997ff is the most distant Type Ia supernova (SN Ia) discovered so far. This z ≈ 1.7 SN is close to several bright, galaxies, and we consider the effects of lensing by those objects on z p 0.6-0.9 the magnitude of SN 1997ff. We estimate their velocity dispersions using the Tully-Fisher and Faber-Jackson relations, corrected for evolution effects, and calculate, applying the multiple-plane lensing formalism, that SN 1997ff is magnified by mag. Due to the spatial configuration of the fore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 33 publications
4
62
0
Order By: Relevance
“…One means of achieving this would be an inspection of the foreground galaxies for each supernova. For example, SN 1997ff at has several foreground z p 1.7 galaxies in its vicinity, leading to a magnification possibly as large as 0.4 mag (Lewis & Ibata 2001;Riess et al 2001;Mört-1 Benítez et al 2002). If the magnification factor could be accurately estimated from the foreground galaxy images, then the supernova brightness could be corrected to its unlensed value.…”
Section: Introductionmentioning
confidence: 99%
“…One means of achieving this would be an inspection of the foreground galaxies for each supernova. For example, SN 1997ff at has several foreground z p 1.7 galaxies in its vicinity, leading to a magnification possibly as large as 0.4 mag (Lewis & Ibata 2001;Riess et al 2001;Mört-1 Benítez et al 2002). If the magnification factor could be accurately estimated from the foreground galaxy images, then the supernova brightness could be corrected to its unlensed value.…”
Section: Introductionmentioning
confidence: 99%
“…(See also Benítez et al 2002, which corrects the observed magnitude of SN 1997ff for gravitational lensing.) SN 1997ff was discovered by Gilliland & Phillips (1998) in a repeat HST observation of the Hubble Deep Field-North, and serendipitously monitored in the infrared with HST/NICMOS.…”
Section: The Smoking Gunmentioning
confidence: 63%
“…(See also Benítez et al 2002, which corrects the observed magnitude of SN 1997ff for gravitational lensing by foreground galaxies.) SN 1997ff was discovered by Gilliland & Phillips (1998) in a repeat HST observation of the Hubble Deep Field-North, and it was serendipitously monitored in the infrared with HST/NICMOS.…”
Section: Early Deceleration Of the Universementioning
confidence: 74%
“…Low-redshift SNe Ia are from Hamuy et al (1996a) and Riess et al (1999a). The magnitude of SN 1997ff at z = 1.7 has been corrected for gravitational lensing (Benítez et al 2002). The measurements of SN 1997ff are inconsistent with astrophysical effects that could mimic previous evidence for an accelerating universe from SNe Ia at z ≈ 0.5.…”
Section: Early Deceleration Of the Universementioning
confidence: 80%